Cytotoxic Evaluation of Malaysian Kelulut Honey on Human Gingival Fibroblast Cell Line using MTT Assay - Zi Yun, Chee; Mohd Nor, Nurul Hafizah; Berahim, Zurairah; Thirumulu Ponnuraj, Kannan (Journal of Dentistry Indonesia, 2021)
Kelulut honey or stingless bee honey is a type of honey produced by stingless bees of the Trigona species where the nest is found in living trees. Objective: The aim of this study was to evaluate the cytotoxic potential of Malaysian Kelulut honey by employing MTT assay on a human gingival fibroblast cell line. Methods:Human gingival fibroblast cell line was cultured in minimal essential medium alpha (α-MEM) with 10% foetal bovine serum and 1% penicillin-streptomycin solution in a 5% CO2 incubator at 37°C in a humidified atmosphere. The cells were seeded at a cell density of 5x103 cells/well in a 96-well culture plate for 24 hours. The cells were treated with seven different concentrations (200, 100, 50, 25, 12.5, 6.25, and 3.125mg/ml) of Malaysian Kelulut honey and incubated in a CO2 incubator. The negative control comprised cells treated with growth media alone. The cell viability was assessed using MTT assay at 24, 48, and 72 hours. The test plate was shaken using a microplate shaker and the absorbance of the solution was measured at 570nm using an ELISA reader with the Magellan software. Statistical analysis of the data was carried out using Kruskal-Wallis test and SPSS 24.0.0 for Windows. A p value Results: There was no cytotoxic effect of Malaysian Kelulut honey on HGF-1 based on the MTT assay at different concentrations and at different time points tested as the cell viability was above 70%. The highest percentage of cell viability at all three different durations of treatment were observed at 3.125mg/ml, whereas the lowest cell viability was observed at 200mg/ml of Kelulut honey concentration. However, statistically significant differences were seen between some of the concentrations at various time points. Conclusion: Since the cell viability of HGF-1 treated with Malaysian Kelulut honey was more than 70% at all concentrations ranging from 3.125mg/ml to 200mg/ml at three different time points (24, 48 and 72 hours), Malaysian Kelulut honey can be considered as non-cytotoxic on human gingival fibroblasts based on MTT assay under the present test conditions.